Pengaruh Kualitas Pelayanan terhadap Kepuasan Konsumen dalam Pembuatan Paspor di Kantor Imigrasi Kelas II Non TPI (Tempat Pemeriksaan Imigrasi) Depok - Nabilla Evanda; Inti Krisnawati (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2023)
Good service quality is crucial and very influential; without the right service, a product will be less attractive to consumers. This study    used quantitative research methods with the aim of knowing the effect of service quality in terms of tangible (physical evidence), reliability, responsiveness, assurance, and empathy on customer satisfaction at the Immigration Office Class II Non TPI (immigration checkpoint) of Depok. The population in this study were all consumers of the Immigration Office Class II Non TPI (immigration checkpoint) of Depok, totaling 23,319 applicants, with a sample of 100  respondents who wanted to apply for a passport. Sampling was done through the distribution of questionnaires. The results showed that the R square value was 0.473 (squaring of the correlation coefficient), or (0.688 x 0.688 = 0.473). R square can be called the coefficient of determination which in this case means that 47.3% of the value of service quality is influenced by the value of customer satisfaction. With these results it can be concluded that service quality has a positive and significant effect on customer satisfaction.